2017
DOI: 10.1016/j.asjsur.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sacrococcygeal pilonidal disease in Turkey

Abstract: We believe that soldiers coming from different regions of Turkey and candidates applying for auxiliary staff positions provide a small sample group resembling a representation of the whole of Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 14 publications
4
44
2
6
Order By: Relevance
“…The exact prevalence remains elusive, but studies using diverse cohorts provide estimates of 4.6–30% for PSD in patients with HS . Therefore, a direct and statistically significant comparison with the general population is still warranted, but the proportion of PSD within this HS cohort seems to be higher than the 1–9% prevalence observed in the general population . The evaluation of the prevalence of PSD among a large cohort of patients with HS represents a complex challenge.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The exact prevalence remains elusive, but studies using diverse cohorts provide estimates of 4.6–30% for PSD in patients with HS . Therefore, a direct and statistically significant comparison with the general population is still warranted, but the proportion of PSD within this HS cohort seems to be higher than the 1–9% prevalence observed in the general population . The evaluation of the prevalence of PSD among a large cohort of patients with HS represents a complex challenge.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15][16][17] Therefore, a direct and statistically significant comparison with the general population is still warranted, but the proportion of PSD within this HS cohort seems to be higher than the 1-9% prevalence observed in the general population. [18][19][20][21] The evaluation of the prevalence of PSD among a large cohort of patients with HS represents a complex challenge. Interestingly, we observed that the IG-HS Prevalence of an inflammatory lesion in the intergluteal fold of patients with hidradenitis suppurativa depending on age.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the disease is generally seen by 6.6%. PSD is seen 16 times more common in men, with being most frequently found in 19-20 years of age in Turkey (8).…”
Section: Discussionmentioning
confidence: 96%
“…The etiology of this disease is still not fully understood (8). Nevertheless, the disease is thought to be associated with hormonal changes that lead to hair obstruction and development of hair follicles in the pilosebaceous glands in the sacrococcygeal region (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of PSD in the general population is about 0.7%, in military personnel it is remarkably higher -with a 9% incidence reported in Turkish soldiers 5 and an increase in Greek soldiers from 4.9% in 1960 to 33% in 1992. 6 Quality of life for patients with PSD PSD may lead to significant time off work due to abscess formation, pain and the need for repeated surgical procedures with long recovery times. It affects the quality of life of sufferers who have difficulty in sitting, must avoid sporting activities and live with the constant worry of recurrence.…”
Section: Prevalencementioning
confidence: 99%